Simple experiments in optics - Aggarwal, R. L. (Roshan Lal), 1937- (Cambridge Scholars Publishing, 2019)
This title compiles over 40 experiments in optics which will be of interest to university, college, and high school students, as well as practicing engineers. These experiments deal with lenses, mirrors, gratings, polarizers, optical windows, optical filters, beam splitters, light sources, and light detectors. Each experiment is clearly described, and concise, easy-to-understand theory is provided to explain the principles underlying them. Appendices provide photos, schematics, specifications, and relevant spectral plots of the optical components, as well as optomechanical components.